2016
DOI: 10.3390/ijms17081369
|View full text |Cite
|
Sign up to set email alerts
|

TNFSF4 Gene Variations Are Related to Early-Onset Autoimmune Thyroid Diseases and Hypothyroidism of Hashimoto’s Thyroiditis

Abstract: The aim of the current study was to examine whether the polymorphism loci of the tumor necrosis factor superfamily member 4 (TNFSF4) gene increase the risk of susceptibility to autoimmune thyroid diseases (AITDs) in the Han Chinese population, and a case-control study was performed in a set of 1,048 AITDs patients and 909 normal healthy controls in the study. A total of four tagging single nucleotide polymorphisms (SNPs) in the TNFSF4 region, including rs7514229, rs1234313, rs16845607 and rs3850641, were genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…Besides, it showed that allele C of rs1179251 increases the teenagers' risk for AITD by 39.7%. Similarly, a pervious paper of ours also reported that there is an association between TNFSF4 gene variations and AITD adolescents [ 19 ]. So these results strongly suggest that the occurrence of thyroid dysfunction in teenagers can be caused by family history, which means the genetic background.…”
Section: Discussionsupporting
confidence: 71%
“…Besides, it showed that allele C of rs1179251 increases the teenagers' risk for AITD by 39.7%. Similarly, a pervious paper of ours also reported that there is an association between TNFSF4 gene variations and AITD adolescents [ 19 ]. So these results strongly suggest that the occurrence of thyroid dysfunction in teenagers can be caused by family history, which means the genetic background.…”
Section: Discussionsupporting
confidence: 71%
“…TNFSF4 , also known as OX40L , could be capable of interacting with its receptor on the late proliferation and sustained activation of T lymphocytes by extending the half-life of the cytokine mRNA ( Vogel et al, 2013 ). Previous studies have shown that genetic variants of TNFSF4/TNFRSF4 are associated with immune disorders such as Behcet’s Disease ( Lu et al, 2016 ), autoimmune thyroid diseases (AITDs; Song et al, 2016 ), and SLEs ( Cortini et al, 2017 ). We found that TNFSF4 rs7514229-T (the mutant allele) was linked to an increased risk of HCV infection, and this effect was more evident in the age, female, lower ALT level (≤ 40 U/L), lower AST level (≤ 40 U/L), HD, and PBD subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Three SNPs (rs10065172/rs4958847/rs13361189) of IRGM gene were selected from the Hapmap CHB data [ 15 ] with the following criteria: minor allele frequency (MAF) > 0.05, Hardy–Weinberg equilibrium (HWE) with P > 0.001, and logarithm of odds (LOD) > 3.0. These three SNPs were genotyped by PCR-based ligase detection reaction (LDR) method used in our previous studies [ 16 18 ]. The PCR condition was initial denaturation at 95°C for 2 min, denaturation at 94°C for 30 s, annealing at 62°C for 90 s, extension at 72°C for 1 min with 40 cycles and final extension at 65°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%